'The curse of Horaeomorphus': taxonomy of misplaced Australian Cyrtoscydmini (Coleoptera: Staphylinidae: Scydmaeninae) - Jałoszyński, Paweł (Zootaxa, 2014)
All Australian species previously placed in Horaeomorphus Schaufuss are revised. None of them was found to belong to this predominantly Oriental genus. Four new genera are established to accommodate these species: Leascydmus gen. n. for Scydmaenus simplicicornis Lea; Scydmaenozila gen. n. for Phagonophana macrosticta Lea (type species) and Phagonophana latipennis Lea; Spinosciacharis gen. n. for Horaeomorphus puncticeps Franz; and Sciacharoides gen. n. for H. thompsoni Franz (type species), H. eucalypti Franz, H. maipotonensis Franz and H. montistamborinensis Franz. Horaeomorphus tasmaniensis Franz is transferred to Sciacharis (Maorinus). Horaeomorphus australiensis Franz is placed as a junior synonym of H. macrostictus (Lea). Phagonophana anthicoides Lea (= Euconnus (Anthicimorphus) anthicoides (Lea)), the type species of Anthicimorphus, is transferred to Horaeomorphus, and Anthicimorphus becomes a junior synonym of Horaeomorphus, which automatically results in numerous new combinations in Madagascan species (ex Anthicimorphus). These, however, almost certainly do not belong to Horaeomorphus and should be treated as incertae sedis within Cyrtoscydmini. These actions result in the following new combinations: i) Australia: Leascydmus simplicicornis (Lea) comb. n.; Scydmaenozila macrosticta (Lea) comb. n.; Scydmaenozila latipennis (Lea) comb. n.; Spinosciacharis puncticeps (Franz) comb. n.; Sciacharoides thompsoni (Franz) comb. n.; Sciacharoides eucalypti (Franz) comb. n.; Sciacharoides maipotonensis (Franz) comb. n.; Sciacharoides montistamborinensis (Franz) comb. n.; Sciacharis (Maorinus) tasmaniensis (Franz) comb. n.; Horaeomorphus anthicoides (Lea) comb. n.; ii) Madagascar: Horaeomorphus aequalis (Franz) comb. n.; H. ambatolampyensis (Franz) comb. n.; H. andasyensis (Franz) comb. n.; H. andasyi (Franz) comb. n.; H. andranomandery (O'Keefe) comb. n. (= Euconnus angustus Franz, 1986b, nec Franz, 1980); H. angustissimus (Franz) comb. n.; H. bialatipensis (Franz) comb. n.; H. comorensis (Franz) comb. n.; H. gomyi (Franz) comb. n.; H. imaitsanus (Franz) comb. n.; H. lacertosus (Franz) comb. n.; H. matsaboryi (Franz) comb. n.; H. nitidulus (Franz) comb. n.; H. paravulgaris (Franz) comb. n.; H. pellifer (Franz) comb. n.; H. sogaensis (Franz) comb. n.; H. tamatavae (Franz) comb. n.; H. tananarivensis (Franz) comb. n.; H. tenuissimus (Franz) comb. n.; and H. vulgaris (C. Schaufuss) comb. n. Additionally, a replacement name Horaeomorphus anthicimadagascanus nom. n. is proposed for Madagascan Euconnus (Anthicimorphus) anthiciformis Franz, 1986b: 238, a junior primary homonym of Chilean Euconnus anthiciformis Franz, 1967. In Australian fauna, seven new species are described: Horaeomorphus verus sp. n.; Leascydmus armstrongi sp. n.; Scydmaenozila mallacootana sp. n.; Scydmaenozila inexpectata sp. n.; Spinosciacharis sassy sp. n.; Spinosciacharis clydensis sp. n.; and Spinosciacharis acheron sp. n. Morphological structures of all treated genera are described and illustrated (including novel characters in previously redescribed Sciacharis (Maorinus)); the current state of knowledge of the Australian Cyrtoscydmini and main problems are discussed.